THE INFLUENCE OF COMPANY SIZE, AUDITOR QUALITY AND AUDIT OPINION ON THE TIMELINESS OF FINANCIAL REPORTING WITH PROFITABILITY AS A MODERATION VARIABLE: (Empirical Study of Banking Companies on the Indonesia Stock Exchange 2020-2022 Period) - Wahyu Safittri; Mukhzarudfa; Ratih Kusumastuti (Transpublika Publisher, 2023)
This research delves into the determinants of financial reporting timeliness, with a specific focus on the moderating effect of profitability. It examines factors such as company size, auditor quality, and audit opinion in the context of 46 banking companies listed on the Indonesian Stock Exchange, utilizing secondary data from the exchange itself. Employing the Partial Least Modeling (PLS-SEM) Structural Equation Modeling approach, the study reveals noteworthy insights. It finds that company size and auditor quality significantly impact reporting timeliness, indicating that larger companies and those with higher-quality auditors tend to report financial information more promptly. Surprisingly, neither audit opinion nor profitability demonstrates a direct influence on financial reporting timeliness, although profitability does act as a moderator, significantly affecting the relationship between company size and reporting timeliness. However, profitability does not play a similar moderating role in relationships involving auditor quality and audit opinion. In summary, this research elucidates the multifaceted nature of factors influencing financial reporting timeliness in the banking sector of the Indonesian Stock Exchange, highlighting the direct impacts of company size and auditor quality alongside the nuanced role of profitability as a moderator in specific relationships.